2006
DOI: 10.1590/s0034-72992006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Fatores etiológicos da deficiência auditiva em crianças e adolescentes de um centro de referência APADA em Salvador-BA

Abstract: Heari ng represents the main source for acquisition of language and speaking skills in childhood. In the first months of life, the hearing impaired child is deprived of sound stimulation in the most important period of development, and consequently, might present emotional, social and linguistic disorders. Therefore, it is of utmost relevance to learn about the main etiological factors that cause the auditory damage to trace a reliable nosological profile, and to take the appropriate measures to prevent and gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 2 publications
1
15
1
5
Order By: Relevance
“…It was observed, therefore, that the time to identify hearing loss is outside of what is considered ideal so that there is no impairment in the development of oral language 1,2 . Given that hearing impairment causes significant sensory deprivation and hearing impaired children in this study were identified after the first year of life, oral language development and later written language tend to be impaired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed, therefore, that the time to identify hearing loss is outside of what is considered ideal so that there is no impairment in the development of oral language 1,2 . Given that hearing impairment causes significant sensory deprivation and hearing impaired children in this study were identified after the first year of life, oral language development and later written language tend to be impaired.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the impact of hearing impairment on communication, it is of great importance that the diagnosis, the adaptation of the hearing device and the beginning of the intervention occur in the first six months of life 2 . In the present study, it was verified that the adaptation of the hearing device occurred on average at 4.2 years old, also far away from the considered ideal time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be emphasized that conductive hearing loss is not restricted to children with HIV/AIDS (21) ; ear infections in the presence of risk factors that may affect the auditory system occur most commonly during childhood (22) . In general, hearing loss in individuals with HIV/AIDS can be caused by opportunistic infections, ototoxic drugs, or direct viral infection (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…A habilidade de compreender a linguagem oral deve ser considerada um dos mais importantes aspectos mensuráveis da função auditiva humana. Na criança com deficiência auditiva, o processo de aquisição e desenvolvimento da linguagem pode ser prejudicado, caso não ocorra diagnóstico e intervenção em tempo adequado para evitar o atraso do desenvolvimento linguístico (SILVA, 2006).…”
Section: Um Pouco Sobre Linguagem Surdez E Educação De Surdosunclassified